Muscle strength and muscle mass in elderly women after cholecalciferol supplementation in Southern Brazil - da Silva, Patrícia Zambone; Schneider, Rodolfo Herberto (PAJAR - Pan-American Journal of Aging Research, 2019)
AimS: Vitamin D is known to be vital in sustaining musculoskeletal functions, with its deficiency may cause muscle weakness and decreased bone mineral density. Vitamin D inadequacy is highly prevalent and its deficiency or insufficiency estimated to affect one billion people worldwide. It causes secondary hyperparathyroidism, bone loss, fractures and it has been associated with a number of other conditions, such as impaired muscle function (1), we decided to verify if there is an association between 25(OH)D status and handgrip strength and with lean muscle mass after cholecalciferol supplementation in elderly women. Methods : We studied fifty-four postmenopausal women with serum 25(OH)D below 30 ng/mL during three months. Cholecalciferol supplementation was divided into two levels according to classification: deficient (10000 units/day) and insufficient (2000 units/day). Changes in biochemical response and in body composition were assessed using dual-x-ray energy absormetry, handgrip strength and blood tests before and after supplementation. Results: The majority of the sample were vitamin D deficient. There was no difference in the deficient group for handgrip strength after the supplementation (p=0,489), but PTH had a statistically significant reduction (p=0.001). Besides, the deficient group had a decrease in lean mass even after the intervention (p=0.006). The results were similar when comparing within results of the insufficient group, however lean mass remained stable (p=0.423). Conclusion: Three-month cholecalciferol supplementation alone in elderly women with doses according to 25(OH)D serum was insufficient to change handgrip strength and total lean muscle mass, however secondary hyperparathyroidism was corrected. *** Força muscular e massa muscular em mulheres idosas após suplementação com colecalciferol no sul do Brasil *** OBJETIVOS: A vitamina D é conhecida por ser vital na manutenção das funções musculoesqueléticas, sua deficiência pode causar fraqueza muscular e diminuição da densidade mineral óssea. A inadequação da vitamina D é altamente prevalente e sua deficiência ou insuficiência estimada afeta um bilhão de pessoas em todo o mundo. Causa hiperparatireoidismo secundário, perda óssea, fraturas e tem sido associada a uma série de outras condições, como função muscular prejudicada, por isso decidimos verificar se há associação entre 25(OH)D e força de preensão manual e com massa muscular magra após suplementação com colecalciferol em mulheres idosas. Métodos : Foram estudadas 55 mulheres na pós-menopausa com 25(OH)D sérica abaixo de 30 ng/mL durante três meses. A suplementação de colecalciferol foi dividida em dois níveis de acordo com a classificação: deficiente (10000 unidades/dia) e insuficiente (2000 unidades/dia). Alterações na resposta bioquímica e na composição corporal foram avaliadas usando a absorciometria de raios-x de dupla energia, força de preensão manual e exames de sangue antes e após a suplementação. Resultados: A maioria da amostra era deficiente em vitamina D. Não houve diferença no grupo com deficiência para força de preensão manual após a suplementação (p=0,489), mas o PTH teve redução estatisticamente significativa (p=0,001). Além disso, o grupo deficiente apresentou diminuição da massa magra mesmo após a intervenção (p=0,006). Os resultados foram semelhantes quando comparados com resultados de grupo insuficiente, porém a massa magra permaneceu estável (p=0,423). Conclusão: A suplementação isolada de colecalciferol por três meses em mulheres idosas com doses de acordo com níveis sérico de 25(OH)D foi insuficiente para alterar a força de preensão manual e a massa muscular total, porém o hiperparatireoidismo secundário foi corrigido. Palavras-chave: Colecalciferol; Força muscular; Idoso.